FACTORS INFLUENCING THE PURCHASING DECISION OF ACCOUNTING SOFTWARE PACKAGES OF ACCOUNTING FIRMS REGISTERED IN THAILAND - Papoomma, Petcharat; Leecharoen, Benjawan; Sangthong, Thaunjai (Journal of MCU Nakhondhat, 2025)
This article aims to review the literature related to factors influencing the purchasing decision of accounting software packages of accounting firms registered in Thailand as a guideline for making decisions to purchase accounting software packages appropriate for the business. The results of the literature review found that the factors affecting the decision to purchase accounting software packages of accounting firms registered in Thailand are: 1) Organizational image factors, which are the perception that customers have of the organization, consisting of corporative Identity, reputation, physical Environment, and contact Personal, 2) Marketing mix factors (7Ps), which include Product, Price, Place, Promotions, Process, People, and Physical Evidence, 3) Program attribute factors, which are a set of characteristics and capabilities, consisting of usability, reliability, utility, maintenance, and safety. 4) Technology acceptance factors, which are the process by which users accept and use new technologies for their benefits, consisting of perceived benefits, perceived ease of use, attitudes toward use, user behavior, and actual use, which will affect the decision to purchase accounting software packages of accounting firms registered in Thailand in five dimensions: problem perception, knowledge seeking, alternative evaluation, purchase decision, and post-purchase behavior, for the benefit of the organization. The decision to purchase accounting software packages is considered an important factor. At accounting firms registered in Thailand, it is important to consider purchasing ready-made accounting software and develop more efficient accounting systems to further increase the value of the business.